STAGED URETHROPLASTY FOLLOWING SEVERE ELECTRIC BURNS TO PERINEUM AND GENITALIA: A CASE REPORT - Patel, Keyur; Nerli, Rajendra; Rai, Shreyas; Bokare, Ashwin; Setya, Nishant (Indonesian Urological Association, 2024)
Objective: This study aims to know the surgical treatment of electrical injuries, perineum, and scrotum. Case(s) Presentation: A 55-year-old male sustained electric burns to the back, perineum and scrotum. The patient failed to void following removal of the catheter 6 weeks later, hence the patient was referred to the urology department for further management. was counselled for a two-phase urethral surgery. Discussion: In our case, the patient had sustained perineal and scrotal burns when he sat over a live wire. This led to the loss of skin and soft tissues, needing massive musculoskeletal and skin grafts. Our patient underwent a number of revision surgeries leading to repeated scarring of the perineal tissues and skin. Conclusion: Electrical injuries to the perinium and genitalia are rare. Hence the surgical strategy of electrical injuries requires a step-wise approach. Initially, conservative debridement needs to performed so as to preserve any tissue of questionable viability and ensure subsequent adequate soft-tissue coverage. The reconstructive surgical procedures bring about satisfactory outcomes. Keywords: Electrical injury, perineum, scrotum, surgical strategy.